REFORMULASI STRATEGI BISNIS - Mahameru, Luky Sanjaya; Hapsari, Raditha Dwi Vata (Jurnal Kewirausahaan dan Inovasi, 2023)
JD.ED Production is a photo and video business from Malang. This research explores the reformulation of the company’s business model and strategies, aimed at identifying the current challenges faced by the company and propose a new business strategy to overcome the problems. Using analyses on the company’s internal and external environment, this research recommends measures to improve their competitiveness in the market. This study uses the Internal-External (IE) matrix; Strength, Weakness, Opportunity, and Threat (SWOT) matrix, and Quantitative Strategic Planning Matrix (QSPM). Based on the research results, this study uses QSPM as the tool of analysis to determine business strategies to be recommended. This research finds that market penetration is the appropriate strategy for JD.ED Production, by which the company is suggested to strive for bigger market share and to improve their business through expansion towards better and larger programs.